IMPRESSIONS” OF MOTHER STELLA DE OXÓSSI, IYA ODÉ KAYODE, THE 5th IYALORISHA OF THE ILÊ AXÉ OPÓ AFONJÁ, ABOUT THE GEOGRAPHIC ATLAS ÁFRICABRASIL OF THE AUTHOR/ GEOGRAPHER RAFAEL SANZIO DOS ANJOS ”“ UNB - Oxóssi, Mother Stella de (Revista Eletrônica: Tempo - Técnica - Território / Eletronic Magazine: Time - Technique - Territory, 2016)
This work that comes to my hands is cause of great joy. The book ÁfricaBrasil, written and organized by the young man Rafael Sanzio, makes us realize that there is a memory that goes beyond all knowledge received at the academy.